Personal web usage in the workplace a guide to effective human resources management - Anandarajan, Murugan 1961-; Simmers, Claire 1950- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2004)
An important aspect of managing human capital in the 21st century workplace is managing the interface between humans and information technology, particularly the World Wide Web. The Web has changed not only how and where business is conducted, but also how and where work is done. Personal web usage has created many desirable organizational outcomes such as, reducing the cost of communication, restructuring how work is performed. However, it has also generated undesirable outcomes, for instance, loss of intellectual property, sexual harassment lawsuits, productivity losses due to surfing usage, security threats, and network bandwidth overload by visiting web sites for travel, leisure, and sports, and news. The mechanisms controlling the interface of individual and institution in this flexible, open, autonomous work environment created by the Web are emergent phenomena, and the lines between legitimate usage and usage are just beginning to be understood. Personal Web Usage in the Workplace: A Guide to Effective Human Resources Management examines topics which embrace a wide array of Personal Web Usage issues such as antecedents of Web usage, frameworks/models of Web usage, Web technologies for monitoring usage, Web usage within other cultures and countries, Measurement issues of Web usage, and the impact of Web usage among others